Soil radon gas emission on the Sivrice (Elazığ, Turkey) fault zone between 2007-2008 years - Bal, Sultan Sahın; Dogru, Mahmut (My University, 2020)
Soil radon gas measurements were made via a sensing system embedded in soil at radon monitoring station, whichwas established in Sivrice Fault Zone of Eastern Anatolia Fault Systems (DAFS) being one of the active faultsystem of Turkey. The occurrence times and magnitude of earthquakes at this zone were compared with the radongas diffusion obtained online from the mentioned station and the results were interpreted in the light of data in theliterature. In this study, it was seen that there is a relationship between the changes in soil radon gas emission andearthquakes. Additionally, according to the analyses on graphs which present the changes in soil radon gasemission taken from station and earthquake lists taken from AFAD (Republic of Turkey Prime Ministry Disasterand Emergency Management Presidency), it was seen that almost all of the earthquakes occur in a decreasingperiod following the increase in radon emission.
Keywords: Fizik; Nükleer; Jeoloji